2011
DOI: 10.1039/c0cc02417a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms in aminocatalysis

Abstract: The mechanisms of the α-, β- and γ-functionalisations of aldehydes and α,β-unsaturated aldehydes by secondary amines are presented and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(111 citation statements)
references
References 133 publications
2
106
0
3
Order By: Relevance
“…General Methods and Materials: NMR spectra were acquired using CDCl 3 (12 g), in EtOH (250 mL) followed by heating or treatment with a solution of KMnO 4 (1.5 g), K 2 CO 3 (10 g), and 10 % NaOH (1.25 mL) in H 2 O (200 mL). Mass spectra were recorder in positive electrospray ionisation (ESI+) or electron impact ionisation (EI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…General Methods and Materials: NMR spectra were acquired using CDCl 3 (12 g), in EtOH (250 mL) followed by heating or treatment with a solution of KMnO 4 (1.5 g), K 2 CO 3 (10 g), and 10 % NaOH (1.25 mL) in H 2 O (200 mL). Mass spectra were recorder in positive electrospray ionisation (ESI+) or electron impact ionisation (EI).…”
Section: Methodsmentioning
confidence: 99%
“…Because enantioselective organocatalysis involving iminium activation [2] provides an excellent procedure for the incorporation of nucleophiles to the β-position of α,β-unsaturated aldehydes, [3] the use of synthetic equivalents of 2-phenylacetic acids as nucleophiles in these processes is very promising for the preparation of highly functionalized 2-phenylacetic acids (Scheme 1). Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…This is well illustrated by the versatility and wide range of different transformations that have been developed in the last decade. A number of theoretical [4] and experimental mechanistic studies [5] for these systems are now available. However, to promote specific reactions the application of dual or cooperative catalyst combinations [6] or the use of (co-catalytic) additives is slowly emerging because this often can prove beneficial for tuning both the reactivity and selectivity of existing catalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Krause, Alexakis, and coworkers showed that amino- [4] and gold catalysis, [20] two current hot topics in the field of catalysis, could be combined effectively in a two-step reaction sequence consisting of an initial organocatalyzed syn-selective conjugate addition to nitroenynes 27, followed by a gold-catalyzed acetalizationcyclization of 29 to give highly enantiomerically enriched tetrahydrofuranyl ethers 28 (Scheme 6). [21] When the two reactions were performed as separate steps, excellent stereoselectivities were observed, and the yields reached 64-76 % for the overall transformation.…”
Section: Typea-2 Reactionsmentioning
confidence: 99%
“…As one of the major hot topics in organic chemistry throughout the past decade, asymmetric organocatalysis [4] has introduced new perspectives with regard to the design and application of one-pot processes in enantioselective transformations. [5] Marked by its robust nature, organocatalysis is probably the most condition-tolerant method within the modern toolbox of asymmetric catalysis.…”
Section: Introductionmentioning
confidence: 99%